Directive Illocutionary and Perlocutionary Act in Now You See Me 1 Movie - Hanna Annisa; Suparto Suparto (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
In speech acts, communication is not only about language but also action. The directive illocutionary is a type of speech act that has the purpose of getting the hearer to do something. It refers to a certain utterance that has certain acts within it. This research aims to analyze the occurrences of directive illocutionary and perlocutionary acts in the Now You See Me 1 movie and figure out how the speaker conveys their intention and how the interlocutor responds to the utterance as the action. The data were analyzed using a descriptive qualitative method based on. Austin's speech act theory and Searle and Vanderveken's directive illocutionary acts theory. The data were collected from the script dialogue of the Now You See Me 1 movie. The results of this research showed there are 120 data of directive illocutionary acts that appear in the movie, namely; asking, commanding, ordering, requesting, suggesting, begging, and forbidding. There are 97 successful perlocutionary acts and 23 unsuccessful perlocutionary acts that occurred in the movie.